Anatomía del leño de Citharexylum montevidense (Spreng) Moldenke, especie forestal nativa de Buenos Aires - Roussy, Luciano (2011)
The aim of this study has been to characterize the wood anatomy of the Citharexylum montevidense (Spreng) Moldenke. Espina de Bañado , which is a native species of Argentina. The material was extracted from five trees which were growing in the Reserva Natural Provincial de Punta Lara (Punta Lara Natural Provincial Reserve) (34° 46' 56'' S, 58° 00' 43'' O; 2 m.s.n.m.) in the province of Buenos Aires. The samples for the study were 5-cm- thick slices which were taken from the main branch of each tree and from an auger sample taken from the trunk. Then, macro and microscopic description of the wood was made. The wood color of the C. montevidense is light yellow or creamy white. Wood has a fine and slightly heterogeneous texture, and the grains are straight, with a grained or slight flowery pattern. The porosity is diffuse to semicircular, with demarcated growth rings. The vessels are small, with an average diameter of 77.4 µm (+/- 12.7), they are 228.6 µm (+/- 44.9) long, and most of them are solitary and radial in pairs. The vessels are abundant with an average of 33 vessels/ mm² (+/- 7). The intervascular punctuations are alternate. The vessels have simple and reticulate perforation plates, without tyloses or contents in the heartwood vessels. The fibers have medium to thick walls of 4.13 µm (+/- 0,77), and an average length of 927 µm (+/- 138). The axial parenchyma is vasicentric and it cames in stripes which are 4-5 cells thick. The woody radiuses were mainly 3 serial ones with a row of square cells at the margins. The anatomic description of the wood coincides with descriptions of other species of the genus.